Lowest places on the planet - Soll, Karen (North Mankato, Minnesota Capstone Press, 2016)
Simple text and full-color photographs describe the lowest places on the planet
The World Around us
1 2 13 15
Keywords: Altitudes -- Juvenile literature; Physical geography -- Study and teaching; Physical geography -- Juvenile literature